Hidden diversity in Senegalese bats and associated findings in the systematics of the family Vespertilionidae - Koubínová, Darina; Irwin, Nancy; Hulva, Pavel; Koubek, Petr; Zima, Jan (Frontiers in zoology, 2013)
INTRODUCTION: The Vespertilionidae is the largest family of bats, characterized by high occurrence of morphologically convergent groups, which impedes the study of their evolutionary history. The situation is even more complicated in the tropics, where certain regions remain under-sampled. RESULTS: Two hundred and thirteen vespertilionid bats from Senegal (West Africa) were studied with the use of non-differentially stained karyotypes and multi-locus sequence data analysed with maximum likelihood and Bayesian methods. These bats were identified as 10 different taxa, five of which were distinctive from their nominate species (Pipistrellus hesperidus, Nycticeinops schlieffenii, Scotoecus hirundo, Neoromicia nana and N. somalica), based on both karyotypes and molecular data. These five cryptic taxa are unrelated, suggesting that these West African populations have long been isolated from other African regions. Additionally, we phylogenetically analysed 166 vespertilionid taxa from localities worldwide using GenBank data (some 80% of the genera of the family) and 14 representatives of closely related groups, together with our Senegalese specimens. The systematic position of several taxa differed from previous studies and the tribes Pipistrellini and Vespertilionini were redefined. The African Pipistrellus rueppellii was basal to the Pipistrellus/Nyctalus clade and the Oriental species Glischropus tylopus was basal to the East Asian pipistrelles within the tribe Pipistrellini. The African genus Neoromicia was confirmed to be diphyletic. Based on GenBank data, Eptesicus was polyphyletic, with the Asian E. nasutus and E. dimissus both supported as phylogenetically distinct from the Eptesicus clade. The subfamily Scotophilinae was confirmed as one of the basal branches of Vespertilionidae. CONCLUSIONS: New taxa and new systematic arrangements show that there is still much to resolve in the vespertilionids and that West Africa is a biogeographic hotspot with more diversity to be discovered.